This place, these people : life and shadow on the Great Plains - Stark, David, 1950- (Columbia University Press, 2014)
Nancy Warner's photographs and David Stark's interviews and reflections provide fresh perspective on the history and culture of a distinctly American phenomenon. Continuing in the tradition of Solomon D. Butcher, who photographed some of the first midwestern settlers in the nineteenth century, and Wright Morris, who combined photographic and verbal accounts of farmers' lives in the twentieth century, Stark and Warner explore a way of life that continues to adapt in the face of wrenching change. This book pairs images of abandoned farm places with the plain-spoken recollections of the people who.